Circulating microRNA changes in heart failure patients treated with cardiac resynchronization therapy: responders vs. non-responders - Marfella, Raffaele; Di Filippo, Clara; Potenza, Nicoletta; Sardu, Celestino; Rizzo, Maria Rosaria; Siniscalchi, Mario; Musacchio, Emilio; Barbieri, Michelangela; Mauro, Ciro; Mosca, Nicola; Solimene, Francesco; Mottola, Maria Teresa; et al. (European journal of heart failure, 2013)
Aims MicroRNAs (miRNAs) play an important role in the pathogenesis of structural alterations of the failing heart through their ability to regulate negatively the expression levels of genes that govern the process of adaptive and maladaptive cardiac remodelling. We studied whether LV reverse remodelling after CRT was associated with changes of circulating miRNAs in patients with heart failure (HF) and dyssynchrony. Methods and results A prospective, non‐randomized self‐control trial was performed in 81 patients with HF eligible for CRT. At baseline, to select the HF miRNA profile, we evaluated the expression of 84 miRNAs (implicated in the pathogenesis of structural alterations of the failing heart) in three groups of patients: healthy subjects (healthy group, n = 15); patients with HF (HF group, n = 81); and patients without HF matched for age, sex, and concomitant disease with HF patients (control group, n = 60). At 12 months, the selected miRNA profile was evaluated in plasma from responder (n = 55) and non‐responder HF patients (n = 26) to CRT. In the test cohort, the HF patients were characterized by lower expression of 48 miRNAs (all P < 0.04) as compared with healthy subjects. In the validation cohort, the HF patients were characterized by lower expression of 24 miRNAs (all P < 0.03) as compared with control patients. At 12 months, 55 patients (68%) were considered responders and 26 non‐responders to CRT (32%). Responders showed an increase in expression of 19 miRNAs (all P < 0.03) compared with baseline expression, whereas in the non‐responders we observed an increase of six miRNAs (all P < 0.05) compared with baseline expression. At follow‐up, miRNAs were differentially expressed between responders and non‐responders. The responders were characterized by higher expression of five miRNAs (miRNA‐26b‐5p, miRNA‐145‐5p, miRNA‐92a‐3p, miRNA‐30e‐5p, and miRNA‐29a‐3p; P < 0.01 for all) as compared with non‐responders. Conclusions In responders, reverse remodelling is associated with favourable changes in miRNAs that regulate cardiac fibrosis, apoptosis, and hypertrophy.